(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he goal of this paper is to present the measures taken in a local context (on the example of Tabasco) to face the impact of the smallpox epidemics at the end of the 19th and the beginning of the 20th centuries in the framework of new control strategies such as public and medical policies which served to reduce mortality rates. his article will shed light on how eicient measures were taken in areas far from the Mexican capital, under diicult conditions such as demographic dispersion, little state control, lack of standard medical protocols, extreme heat, lack of roads and an emphasis on inland water transport.